Visual Konsep Tokoh untuk Fine Dining Projection Mapping dengan judul "Si Dulang" - Christine Mersiana Lukmanto (ULTIMART Jurnal Komunikasi Visual, 2022)
The internet and social media have established the world of fine dining and animation. There is an increase of competition in the business since people care more than just how the food taste or how the food is being displayed but also how they are presented to the table. One aspirating aspect on the presentation is by utilizing projection mapping in presenting an animated film that provide knowledge, information and entertainment to the customers that were measured to the themes, ideas and concepts of typical Indonesian food. This cutting-edge digital art in the form of a hybrid animation is believed to help both fine dining and animation industry to broaden the areas. This research purpose is to create characters’ visual concept for ‘“Si Dulang”’. There are two characters that will be discussed in this journal which are Dulang the adventurer kid and Barong the mythology creature. In order to visualize the characters, the researchers have to understand the mythology figures in Bali and thus literature studies and observations of various projection mappings will be used as research methods. The outputs of this research are prototype of animated film, intellectual property right of character figures and art book. Keywords: projection; mapping; character; visual concept; hybrid animation.